2020
DOI: 10.1002/batt.202000060
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Aqueous Zinc‐Ion Batteries with Mild Electrolytes: A Comprehensive Review

Abstract: Prof. Jiang's research focuses on energy storage devices, including lithium, sodium, and zinc ion batteries, which are supported by NSFC and major basic research projects of Shandong natural science foundations. Figure 1. a) Diagram of potential-pH value (Pourbaix diagram) of Zn in aqueous solutions. Reproduced with permission from Ref. [25]. Copyright 2015, Wiley-VCH. b) Discharge mechanism of a ZnÀ MnO 2 alkaline battery depicting main side reactions on both electrodes. Reproduced with permission from Ref. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 294 publications
(1,017 reference statements)
0
43
0
Order By: Relevance
“…Continued uneven deposition can lead to variations in localized current density, resulting in large overpotential and zinc dendrites growth. [3] The severe zinc dendrites growth can cause penetration of the separator and short circuiting of the battery passable fence" on the surface of Zn metal anode, which can make the deposition of zinc ion refined and uniform. By means of the 20-25 µm NTP coating, the Zn/Zn 2+ cycling demonstrates a lifespan up to 260 h at the current density of 1 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued uneven deposition can lead to variations in localized current density, resulting in large overpotential and zinc dendrites growth. [3] The severe zinc dendrites growth can cause penetration of the separator and short circuiting of the battery passable fence" on the surface of Zn metal anode, which can make the deposition of zinc ion refined and uniform. By means of the 20-25 µm NTP coating, the Zn/Zn 2+ cycling demonstrates a lifespan up to 260 h at the current density of 1 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Continued uneven deposition can lead to variations in localized current density, resulting in large overpotential and zinc dendrites growth. [ 3 ] The severe zinc dendrites growth can cause penetration of the separator and short circuiting of the battery system. [ 4 ] Meanwhile, the side reaction can lead to serious capacity fading.…”
Section: Introductionmentioning
confidence: 99%
“…[30,97] However, many previous works have indicated that the storage mechanism in AZIBs would be also greatly influenced by the properties of aqueous electrolyte, such as pH value, and the species of additive and Zn-salts, thus making the actual reaction process more complicated, and many controversial issues are still remaining. [99][100][101] Excepting the Zn 2+ , H + would also exists in the acidic electrolyte, such result would lead to a competitive reaction mechanism between Zn 2+ and H + during the charging and discharging process. [102] Until now, several types of mainstream storage mechanisms have been formally proposed, which can be included as follows: 1) Zn 2+ insertion/extraction mechanism; 2) ions/molecules co-insertion/extraction mechanism; 3) H + insertion/extraction mechanism; and 4) conversion reaction mechanism.…”
Section: Storage Mechanism Of Cathode Materialsmentioning
confidence: 99%
“…Moreover, we compared the utilization of anode of Te/MnO 2 and Te/Ni(OH) 2 batteries with other ZIBs; the high utilization of Te anode achieved (50.1% for the mild system and 38.9% for the alkaline system) is remarkably higher than Zn anode in various ZIBs (Figure 5h and Table S1, Supporting Information). [16,27,36,44] We also compared the performance of Te/MnO 2 and Te/Ni(OH) 2 batteries with other ZIBs, including normal Zn metal batteries and non-Zn metal batteries in terms of cycle life and capacity (based on the total mass of anode and cathode), which is shown in Figure 5i. [16][17][18]44] Apparently, long cycling life and high capacity achieved by the Te anode is superior to conventional ZIBs with Zn metal as anode (capacity < 60 mAh g −1 anode+cathode ).…”
Section: Practicability Of Te Anode-based Zinc Ion Batteriesmentioning
confidence: 99%